Interactions among brand credibility, brand affect and brand behavioural intentions in professional sports teams: the moderation role of brand affect and live stadium attendance - Kadir Yağız (Nicolaus Copernicus University in Toruń, 2021)
The purpose of this study was to investigate the effect of brand credibility and brand affect on behavioural intentions of professional sports team consumers toward their teams, and also investigating the moderating role of their brand affect level, live attendance frequency in stadium and gender on this relationship. Results showed that brand credibility and brand affect had a significant and positive effect on behavioural intentions. Also, the importance sports consumers attached to brand credibility of a team in respect to their behavioural intentions differed at their varying level of brand affect, live attendance frequency and gender. Through this study it was presented to sports managers about the mechanisms through which brand credibility exerts its effect on consumers' behavioural intentions across the varying level of brand affect, live attendance frequency and gender which would guide in their strategic brand management implementations.